Kolaborasi dan Peran Bank Sentral di Tengah Pandemic Covid-19 - Fuddin, Muhammad Khoirul; Soelistyo, Aris; Setyowati, Ika Yuli; Capridasari, Denita; Arista, Linda; Izzah, Evita Nurul (LPPM Universitas BSI, 2023)
The purpose of this research is to find out what collaborations or collaborations have been carried out by the central bank in dealing with the Covid-19 pandemic that has occurred in recent years, including Bank Indonesia as the central bank in Indonesia. In this regard, we will also look at the role of the central bank in dealing with the Covid-19 pandemic. The research we conducted aims to examine scientific articles about the discussion of